Border Crossings between Georgia and Turkey: The Sarp Land Border Gate. Issue 2 (3rd April 2017) - Toktaş, Şule; Çelik, Nihat
ABSTRACT: The Sarp land border gate between Turkey and Georgia has become Turkey's gateway to the East in recent years. With a large number of individuals crossing every day, it is also a labour gate, where irregular Georgian immigrants cross the border for work in Turkey. In general, border policies are constructed and reconstructed in a dynamic process in which economic, security, ethnopolitical, geopolitical and cultural paradigms interact. The aim of this paper is to observe the complementary and conflicting relationship and negotiation process between economic and security paradigms in particular, with a focus on the perceptions of the officers of the border administration and state bureaucracy at the local level. To this end, field research was carried out consisting of interviews with Turkish state officials responsible for immigration and border crossing in the Sarp gate region. The article sheds light on the interaction between various agencies, actors and stakeholders in border policymaking at the regional level. It also elaborates on the profiles both of incoming immigrants employed as irregular workers and of deportees. The results of the qualitative study show that the dominance of the economic paradigm that underlies the main framework of Georgia-Turkey relations overrides security concerns between the two countries, thus necessitating a more flexible implementation of laws. The field research illustrates that implementation of laws and regulations at the local level varies and while some groups of irregular immigrants are allowed to work, others are not and, what is more, are deported.